Efficacy and safety of sublingual immunotherapy using a combination of Dermatophagoides pteronyssinus and Blomia tropicalis extracts in patients with allergic rhinitis: A randomized, double-blind, placebo-controlled trial - Priscilla Rios Cordeiro Macedo, MD, MSc; Priscila Moraes, MD; Luísa Karla Arruda, MD, PhD; Fábio Fernandes Morato Castro, MD, PhD; Jorge Kalil, MD, PhD; Clóvis Eduardo Santos Galvão, MD, PhD (World Allergy Organization Journal)
Background: Allergen immunotherapy is the only treatment that may modify the natural course of allergic diseases. Sublingual immunotherapy (SLIT) is a promising treatment, especially for children. Few studies currently exist related to optimal dosing for Blomia tropicalis. Methods: This was a double-blind, randomized, placebo-controlled trial of SLIT to treat house dust mite-induced Allergic Rhinitis (AR). A total of 65 patients, ages 12–16 years, were treated for 12 months and randomized into SLIT versus placebo. The SLIT group received a combination of Dermatophagoides pteronyssinus and Blomia tropicalis allergens. Sensitization was confirmed by skin prick test or serum specific IgE. Total Nasal Symptom Score (TNSS), Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ), current treatment, and need for medication to control symptoms were ascertained during the study. Total serum IgE, serum specific IgE, and IgG4 levels for Der p 1 and Blo t were assessed at baseline and, 6 and 12 months after treatment. Results: There was no significant difference in the number of adverse events between groups. The SLIT group showed a significant reduction in antihistamine use to control symptoms (p < 0.0001) compared to placebo. There was no significant change in serum total IgE, serum specific IgE, and IgG4 for either allergen when comparing the SLIT and placebo groups. Conclusion: After 1 year, SLIT using a dose of 1 mcg of Der p 1/day and 753 UBE of Blo t/day lowered the need for medications for break-through symptoms, with a good safety profile.''